Human’s Experience at Turning-point in Vytautas Martinkus’s Novel “Simonija”: the Aspect of Literary Ethics - Tutlytė, Kristina (Respectus Philologicus, 2020)
The author of the thesis uses Literary Ethics as a theoretical instrument and analyses the portrait of human dealing with turning-point in Vytautas Martinkus’s novel Simonija. The novel corresponds to the features of the turning-point literature marked in the dissertation of V. Katinienė: the thematic level emphasizes a change of historical (political) order and its existential problems; in thoughts, dreams, memories characters go back to the period of totalitarianism; the contrast between “homo sovieticus” and individuals of the free world is emphasized. The analysis of ethical conflicts in Simonija is presented, having in mind specific cultural context during the Soviet period and emphasizing the process of writing as a particular ethical situation and a way to reflect human’s experience. Vytautas Martinkus offers appropriate “snoumenizm” notion for summarizing human’s experience during the Soviet periodperiod. In essence, dehumanizing, painful experience of the Soviet era does not abandon human even in the period of freedom and forces him to go back to the past – physical presence in the world of restored independence does not free him from inner stagnation. In this paper, it is shown that Literary Ethics is asuitable theoretical instrument in order to analyze text about human’s experience at turning-point.